MOMP in the absence of BH3-only proteins - García Sáez, Ana J. (Genes Dev, 2016)
The minimum requirement for mitochondrial apoptosis has been controversial ever since the discovery of BCL-2 as a cell death regulator. In this issue of Genes & Development, O'Neill and colleagues (pp. 973–988) end a long-standing debate by creating a cellular system free of BCL-2 family proteins, thereby identifying the outer mitochondrial membrane rather than BH3-only proteins as the only requirement for BAX/BAK activation and mitochondrial outer membrane permeabilization (MOMP).